A Novel Domain‐Confined Growth Strategy for In Situ Controllable Fabrication of Individual Hollow Nanostructures. Issue 5 (26th February 2018) - Tang, Luping; He, Longbing; Zhang, Lei; Yu, Kaihao; Xu, Tao; Zhang, Qiubo; Dong, Hui; Zhu, Chao; Sun, Litao
Abstract: The manipulation and tailoring of the structure and properties of semiconductor nanocrystals (NCs) is significant particularly for the design and fabrication of future nanodevices. Here, a novel domain‐confined growth strategy is reported for controllable fabrication of individual monocrystal hollow NCs (h‐NCs) in situ inside a transmission electron microscope, which enables the atomic scale monitoring of the entire reaction. During the process, the preformed carbon shells serve as nanoreaction cells for the formation of CdSeS h‐NCs. Electron beam (e‐beam) irradiation is demonstrated to be the key activation factor for the solid‐to‐hollow shape transformation. The formation of CdSeS hollow NCs is also found to be sensitive to the volume ratio of the CdSe/CdS NCs to the carbon shell and only those CdSe/CdS NCs with a volume ratio in the range 0.2–0.8 are successfully converted into hollow NCs. The method paves the way to potentially use an e‐beam for the in situ tailoring of individual semiconductor NCs targeted toward future nanodevice applications. Abstract : Individual hollow semiconductor nanocrystals (NCs) are formed by electron‐beam‐induced domain‐confined growth of partially sublimated NCs. Experimental parameters can be varied to select individual NCs from an ensemble to form hollow structures. This method therefore provides an interesting pathway for the precision machining of single structures for nanodevice fabrication.